Design of New n‑Type Porphyrin Acceptors with Subtle Side-Chain Engineering for Efficient Nonfullerene Solar Cells with Low Energy Loss and Optoelectronic Response Covering the Near-Infrared Region - Tsai, Ming-Chi; Hung, Chieh-Ming; Chen, Zi-Qin; Chiu, Yi-Chieh; Chen, Hsieh-Chih; Lin, Ching-Yao (ACS applied materials & interfaces, 2019)
A series of tailor-made highly efficient and near-infrared (NIR) porphyrin-based acceptors is designed and synthesized for fullerene-free bulk-heterojunction (BHJ) organic solar cells. Constructing BHJ active layers using a PTB7-Th donor and porphyrin acceptors (P-x), which have complementary absorption, accomplishes panchromatic photon-to-current conversion from 300 to 950 nm. Our study shows that side chains of the porphyrin acceptors fairly influence the molecular ordering and nanomorphology of the BHJ active layers. Significantly, the porphyrin acceptor with four dodecoxyl side chains (P-2) achieves an open-circuit voltage (V OC) of 0.80 V, short-circuit current density (J SC) of 13.94 mA cm–2, fill factor of 64.8%, and overall power conversion efficiency of 7.23%. This great performance is attributable to the ascendant light-harvesting capability in the visible and near-infrared region, a high-lying LUMO energy level, a relatively high and more balanced carrier mobilities, and more ordered face-on molecular packing, which is beneficial for obtaining high V OC and J SC.